ANALISIS PENERAPAN ACTIVITY BASED MANAGEMENT UNTUK MENINGKATKAN EFISIENSI PADA HOTEL GRAN CENTRAL MANADO - Muskitta, Christanty J R; Morasa, Jenny; Alexander, Stanly (Universitas Sam Ratulangi, 2018)
The creation of an increasingly advanced business world it affects the increasingly fierce business competition. This competition not only occurs in the manufacturing industry but also in the service industry. In order to survive and win the competition, the hotel must increase its competitive advantage with the efficiency of managing the activity without reducing the quality provided to the customer. Activity Based Management is a method to improve efficiency. The purpose of this research is to try to apply activity based management method to improve efficiency at Hotel Gran Central Manado by identifying activity after that in analysis including activity not value added, eliminated so that can be reduced. The method used is descriptive method. The result of the research by applying activity based management method, found in room division of activity which is not added value and doing cost reduction that is not added value so that the efficiency increase without reducing the quality of service given to the customer.Keywords : Activity Based Management, Activity, Efficiency